Psychiatric Outpatients After the 3.11 Complex Disaster in Fukushima, Japan - Arinobu Hori (Ubiquity Press, 2017)
Background After the 3.11 complex disaster, fear of radioactive contamination and forced evacuation influenced a number of residents to seek psychiatric care. Objectives This study assessed the sequential changes in the number of new outpatients and patients with acute stress disorder (ASD), post-traumatic stress disorder (PTSD), adjustment disorder, and depression after the Fukushima disaster. Methods We distributed questionnaires to 77 psychiatric institutions to determine the number of new outpatients between March and June in 2010, 2011, and 2012. Findings There were 771, 1000, and 733 new patients in 2010, 2011, and 2012, respectively. We observed a statistically significant increase in new patients with ASD or PTSD and a significant decrease in patients with depression in 2011, which returned to predisaster levels in 2012. Conclusions There were time- and disease-dependent changes in the numbers of psychiatric care-seeking individuals after the 3.11 complex disaster in Fukushima.